Clinical Semiology at the Technology Age: the New Cardiology - Cardim, Nuno (2015)
Keywords: Cardiology/education; Cardiovascular Diseases/ultrasonography; Cardiovascular Diseases/radiography; Diagnosis, Differential; Echocardiography; Education, Medical, Continuing.